THE INFLUENCE OF COMMITMENT AND WORKLOAD ON EMPLOYEE PERFORMANCE AT LAKE TOBA INTERNATIONAL MEDAN HOTEL - Aristo Faye Pasaribu; Richard Elyas; Hodmiantua Sitanggang; Melias Metami Latersia; Marudut Sianturi (JURNAL PROINTEGRITA, 2019)
Employee performance is very important not only for the employee itself but also for the organization as a whole, so that every organization gives serious attention to the achievement of employee performance, which is accompanied by all efforts to improve it, so that the work target of the organization can be achieved properly. This study aims to determine the influence of commitment and workload on employee performance at Danau Toba International Hotel Medan, both partially and simultaneously. The population of this study were employees who worked at the Lake Toba International Medan Hotel, which numbered 50 people. For total population are less than 100 people, thus total population taken as samples. Data was collected using a questionnaire and documentation. While the data analysis techniques used are correlation test, t test, F test and coefficient of determination. The results of study showed that the commitment variable had a positive and significant influence on the performance of employees of the Danau Toba International Hotel Medan. The higher commitment causes employee performance to increase. Workload variables have a positive and significant influenceonemployees performance. The higher the workload, the higher the performance of hotel employees. Commitment and workload variables simultaneously have a significant influence on employess performance. The determination coefficient of 85.80% in employee performance can be explained by commitment and workload simultaneously, while the remaining 14.20% is explained by other factors, such as competency variables and work discipline.